1986
DOI: 10.1007/bf00925488
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil responses of permissive and nonpermissive hosts to the young adult worms ofAngiostrongylus cantonensis

Abstract: Blood and bone marrow eosinophilia was assessed in nonpermissive (guinea pigs) and permissive (rats) hosts following the pulmonary arterial transfers of live or dead young adult worms of Angiostrongylus cantonensis. Guinea pigs showed a marked eosinophilic response to live worms but only a slight response to dead worms. Neither IgE nor haemagglutinating antibodies correlated with the induction of this eosinophilia. In contrast, the rat responded to neither form of the young adult worm. When the guinea pig and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…These results are in line with other researchers' reported findings that worm degeneration and eosinophil degranulation in non-permissive hosts may differ from those in their normal definitive hosts, and the growth rates of A. cantonensis larvae in mice are less than in rats (Ishida and Yoshimura 1986). Different hosts have different immune responses, so their cytokines are also diverse.…”
Section: Discussionsupporting
confidence: 82%
“…These results are in line with other researchers' reported findings that worm degeneration and eosinophil degranulation in non-permissive hosts may differ from those in their normal definitive hosts, and the growth rates of A. cantonensis larvae in mice are less than in rats (Ishida and Yoshimura 1986). Different hosts have different immune responses, so their cytokines are also diverse.…”
Section: Discussionsupporting
confidence: 82%
“…The major pathological damages in human CNS induced by A. cantonensis infection include; (1) meningitis with a predominance of eosinophils and plasma cells; (2) multiple microcavities, tortuous tracks, and microscopic hemorrhage surrounded by inflammatory cells and neuron lesions in the brain and spinal cord parenchyma; (3) granulomatous response to the dead worms; (4) nonspecific vascular reactions, thrombosis, and aneurysm formation [ 42 , 44 ]. In A. cantonensis -infected mammalian brains (permissive host rats and nonpermissive hosts, including mice, rabbits, and guinea pigs), similar pathological changes were also found in CNS [ 23 , 24 , 28 , 29 , 45 , 46 ]. In this study, plaque-like lesions also showed in various regions in infected animals.…”
Section: Discussionmentioning
confidence: 84%